Double Life. Illusion - Disillusion - Boer, Nelle (Aesthetic Investigations, 2015)
In order to make my life and therefore my art more exciting I often imagine being someone else. While working on art projects, usually for several months, I have lived double lives as art historians and political scientists, but mostly as artists who should have been famous. To trick my audience into believing the fantasy figures I fabricate are real, I use circumstantial evidence. But with the help of that same audience, the double lives I live become far more interesting. It is their imaginative power that really brings my alter egos to life.